Biochar and nutrient dynamics: Impact on growth, development and yield of wheat (Triticum aestivum L.) - Vishvajeet, D J; Santosh, K (Plant Science Today, 2025)
The Trans-Gangetic Plains are among the most extensively cropped agro-ecological zones of India, with wheat (Triticum aestivum L.) being the most widespread rabi season crop. Crop residue and nutrient management are crucial in this system. The experiment was conducted using a split-plot design with 3 replications. The main plot factors consisted of 3 biochar types: paddy straw biochar (B1), red gram stover biochar (B2) and cotton stover biochar (B3) with sub-plot factors included 4 nutrient management strategies: 100 % recommended dose of fertilizers (RDF, N1), 70 % RDF + 2 foliar sprays (FS) of liquid compost (N2), 70 % RDF + 2 foliar sprays of nano DAP (N3) and control (N4). Results revealed that, application of cotton stover biochar significantly increased plant height by 3.5 % and 10.06 %, dry matter accumulation (DMA) by 0.51 % and 1.2 %, chlorophyll index by 0.9 % and 1.6 %, grain yield by 3.7 % and 9.4 % and straw yield by 2.9 % and 6.9 %, over red gram and paddy straw biochar respectively. Similarly, application of 100 % RDF increased growth, yield attributes and the yield of wheat, which was statistically similar to N2. However, N2: 70 % RDF + liquid compost enhanced the grain yield by 3.37 % and the straw yield by 3.13 %. Hence, application of cotton stover biochar with 70 % RDF + FS of liquid compost shows better performance across all growth and yield attributes and the yield of wheat. In the future, biochar has the potential to bioeconomy models, thereby making significant contributions to climate change mitigation, supporting carbon trading initiatives and enhancing circular bioeconomy models.